Evoluç\~ao da execuç\~ao orçamentária do ministério da ciência, tecnologia e inovaç\~ao entre 2001 e 2010 - Glauber Pimentel de Queiroz; Luiz Ricardo Cavalcante (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– The aim of this paper is to analyze the budget execution of the Brazilian Ministry of Science, Technology and Innovation (MCTI) in the period between 2001 and 2010 in order to evaluate if changes in its composition would indicate a greater emphasis on systemic innovation policies. Data collection and analysis was based upon the four main science, technology and innovation (ST&I) actions of the Ministry since the early 2000s: i) expansion and consolidation of national ST&I actions; ii) promoting technological innovation in industry; iii) research, development and innovation in strategic areas and iv) science, technology and innovation for social development. The analysis of the budgetary performance of the MCTI indicates that the relative position of the first (expansion and consolidation of national ST&I actions) and second (promoting technological innovation in industry) areas was inverted during the 2000s. The increasing focus on promoting technological innovation in industry suggests a match between the budgetary performance of the ministry and the formal documents that record explicit public policies on ST&I, which emphasize more systemic and less linear instruments. However, even resources explicitly allocated in the second area are subject to disputes among science foundations, academic communities and industry. The first area total budget, which includes resources to academic grants, to research units and to a sectoral fund aimed at improving universities infrastructure (CT-Infra), increased progressively during the decade. The growth of the first area budget can be credited to the increasing resources allocated for the CT-Infra, which grew by around 200% during the period. A significant increase was observed in the resources allocated in the sectoral funds associated with the second area, especially the ones associated to oil and gas (CT-Petro) and energy (CT-Energia). Because of its focus on fields considered critical to the national development (such as nuclear energy, aerospace and natural resources), the third area is more likely to suffer changes in its resource allocation profile. This explains the changes in 2005 (due to increases in resources directed to nuclear energy) and in 2009 (due to satellites development). Finally, the resources allocated in the fourth area (science, technology and innovation for social development) grew more systematically from 2005 onwards because of budget amendments by the parliament. As a result, the increase in this area is marked by ups and downs associated to budget constraints. In face of these results, it is argued that during the 2000s MCTI has managed to match its budget execution to the documents in favor of a more systemic approach to the ST&I policies, in spite of the presence of some elements more closely associated with the linear innovation model and with the incremental nature of the budget process.
Keywords: O3; O31; O38; H61; 330